Simulación numérica CFD de la estructura de control y del sistema de compuertas radiales – Represa El Quimbo (2017)
The general objective of this study is related to the development of a numerical model in 2D without considering the effect of stacks and stirrups in the water, at 1:70 scale, under conditions of permanent flow of control structure and system Of radial gates - El Quimbo Dam, from the implementation of ANSYS Fluent 17.0 software. The hydrodynamic analysis of the structure was performed under free surface conditions with different hydraulic loads (H / HD = 0.5, H / HD = 1, H / HD = 1.33), for different flows (3024 m3 / s, 3312 m3 / S, 4261 m3 / s, 5210 m3 / s, 11,888 m3 / s), and for openings of 704 msnm, 706.9 msnm, 709.4 msnm, 712 msnm and 724.6 msnm. The behavior of the residual values ​​was evaluated until the level of convergence was obtained. In addition, the mesh independence was studied to determine the optimum level of refinement. The inlet and outflow boundary conditions of the flow, the behavior of the water sheet through the landfill, the discharge coefficients, the approach velocities and the variations in the pressure fields developed in the radial gate system , In the fast and in the deflector. Subsequently, the numerical model was validated, based on the comparison of the numerical results with the theoretical data made by INGETEC and the data of the tests carried out in the physical model developed by the National University of Colombia (Manizales site). Finally, the capacity of the numerical model to simulate the hydraulic behavior of the physical model was evaluated, establishing the degree of variation of the real data with the data obtained through the numerical simulation.